Ebola imaginaries and the Senegalese outbreak: anticipated nightmare and remembered victory - (:unkn) unknown (My University, 2020)
Abstract Although Senegal experienced a single ‘imported’ Ebola case, this epidemiological event was experienced locally as a full outbreak in its first phase. Two imaginaries developed in parallel: the nightmare of an uncontrolled infectious threat bringing social disruption and spreading through Senegal to other continents; and the vision of an efficient mobilization of the national public health system as a model for other West African countries hit by Ebola. Based on field data, the article analyses how these antagonistic imaginaries shaped the national narrative of the epidemic and affected its interpretations on an international level. The health system's capacity to control the epidemic gradually dominated the nightmare fantasy in the national narrative, and has effectively articulated a technical discourse and protective measures rooted in lay perceptions – in particular the physical distancing of risk. Charles Rosenberg's model for analysing the temporality of epidemic narratives, which distinguishes four phases (progressive revelation, agreement on an explanatory model, political and ritual action, and closure), proved to be relevant, provided that two phases were added. These phases – before the beginning and after the end of the epidemiological event – appear significant in terms of the social production of the meaning of epidemics.
Keywords: African Research